Essence of state and legal function of the prosecutor in criminal trial of the Kyrgyz Republic (Journal of actual problems of jurisprudence, 2019)
The author carried out the analysis of the procedural status and function of bodies of supervision in moderncriminal legal proceedings of the Kyrgyz Republic, in particular public prosecutor's supervision of legalityin criminal procedure activity of the investigation authorities, promoting providing guarantees of legality atinvestigation of crimes.Keywords: attorney, criminal procedure, the functions of the state, a consequence of the law.